External Stresses Affect Gonococcal Type 4 Pilus Dynamics - Kraus-Römer, Sebastian; Wielert, Isabelle; Rathmann, Isabel; Grossbach, Jan; Maier, Berenike (Frontiers in Microbiology, 2022)
Bacterial type 4 pili (T4P) are extracellular polymers that serve both as adhesins and molecular motors. Functionally, they are involved in adhesion, colony formation, twitching motility, and horizontal gene transfer. T4P of the human pathogen Neisseria gonorrhoeae have been shown to enhance survivability under treatment with antibiotics or hydrogen peroxide. However, little is known about the effect of external stresses on T4P production and motor properties. Here, we address this question by directly visualizing gonococcal T4P dynamics. We show that in the absence of stress gonococci produce T4P at a remarkably high rate of ∼200 T4P min–1. T4P retraction succeeds elongation without detectable time delay. Treatment with azithromycin or ceftriaxone reduces the T4P production rate. RNA sequencing results suggest that reduced piliation is caused by combined downregulation of the complexes required for T4P extrusion from the cell envelope and cellular energy depletion. Various other stresses including inhibitors of cell wall synthesis and DNA replication, as well as hydrogen peroxide and lactic acid, inhibit T4P production. Moreover, hydrogen peroxide and acidic pH strongly affect pilus length and motor function. In summary, we show that gonococcal T4P are highly dynamic and diverse external stresses reduce piliation despite the protective effect of T4P against some of these stresses.